That noodle life : soulful, savory, spicy, slurpy - Le, Mike; Le, Stephanie (Workman Publishing, 2022)
"Oh, noodles! You're so much fun. You're so beloved! All your magical shapes, flavors, and textures. But no one obsesses over you quite like Mike Le and Stephanie Le, the-husband-and-wife team who are superstars in the food blog world. Their humbly named iamafoodblog boasts 186,000 followers on Instagram and receives 500,000 page views each month-and in it they profess their undying love for noodles in the most delicious, clever, and visually striking ways. That Noodle Life is their 75-recipe celebration of the myriad pleasures of noodles. And let's just say it goes way beyond spaghetti and ramen. Inspired by the noodle- and macaroni-crazed cuisines of Asia, Italy, and the global melting pot, they dish up high-impact, soulful, slurpable flavor with minimal fuss. Gorgeous full-color photographs of every dish enhance the lively and sophisticated spreads. Dig into comfort noodles: Really Savory Sunday Sauce with Tagliatelle and French Onion Mac and Cheese. Quick weeknight noodles: Flash-Fried Ribeye with Crispy Chow Mein and Stay in Tonight Sesame Chili Oil Noodles-faster than takeout and far better. Sexy Date Night Noodles: Double Lobster Chitarra, Miso Clam Linguine, Bone Marrow and Beef Brisket Pho. And how to upgrade instant noodles to make them shine, recipes for making noodles from scratch, notes on essential ingredients, and noodle etiquette, including how to use a ramen vending machine in Japan. Plus, who wouldn't want to participate in the Lasagna Bracket Competition?"--